Health Literacy Improvement and Use of Digital Health Services in Aged People: A Systematic Literature Review - Maedeh Ghorbanian Zolbin; Shahrokh Nikou (International Telecommunications Society (ITS), 2021)
The low level of health literacy skills often found in elderly people has been associated with a significant risk of poor access to health services and poor health status and makes it more likely that they will be prevented from obtaining and understanding the basic health information and services needed to make appropriate health decisions. Therefore, empowering the older population with health literacy skills could enable them to benefit from the use of various digital health sources, such as telemedicine, webpages, or other digital platforms, to improve their health quality and enable them to live independently for longer. The purpose of this paper is to perform a systematic review to analyse and evaluate studies that explored the relationship between health literacy skills and the use of digital health platforms in the context of elderly people. To do so, four main databases - Medline, Scopus, Web of Science, and PubMed -were searched based on the following inclusion criteria: (i) no geographical limitation, (ii) written in English, (iii) participants were aged ≥ 65 years, and (iv) studies were published between 2000 and 2020. By applying the inclusion and exclusion criteria for further analysis, the final dataset comprised 32 articles, which were analysed using the Preferred Reporting Items for Systematic Reviews (PRISMA) model. The results show that four different intervention methods could be used to increase elderlies' health literacy skills in the case of using digital health services. Besides, before implementing any training sessions, barriers of learning shall be identified and tackled.
Keywords: 330; Aging; Digital health service; E-health literacy; Elderly people; Health literacy; Intervention; Senior population; Systematic literature review